Chronic Hepatitis C in Western Canada: A Survey of Practice Patterns among Gastroenterologists in Alberta and British Columbia. Issue 1 (2014) - Pai, Rohit; Ramji, Alnoor; Lee, Samuel S; Wong, Winnie W; Yoshida, Eric M
Abstract : OBJECTIVE: To survey gastroenterologists in British Columbia and Alberta with regard to awareness of chronic hepatitis C virus (HCV) management and practice patterns among physicians who treat and do not treat HCV-infected patients. METHODS: An anonymous two-page mail survey was distributed to actively practicing adult gastroenterologists in British Columbia and Alberta. Among physicians who treated HCV patients, respondents answered assessment of fibrosis pretreatment, measurement of rapid virological response, prescription of protease inhibitors (PIs), barriers to using these agents and referral patterns. For those who did not treat HCV, referral of patients for treatment and to whom was assessed. RESULTS: Seventy-seven of 166 individuals completed the survey (46% response rate). Most (49%) practiced in academic or large community (42%) settings. Chronic liver disease comprised <25% of individual practice in 71%. Forty-eight (62%) treated HCV and two-thirds prescribed a PI. Barriers to prescription included unfamiliarity (six of 16), lack of allied health (five of 16) and few suitable patients (seven of 16). Pretreatment liver biopsy was performed by 33% (16 of 48) and 69% (33 of 48) used noninvasive measures. Rapid virological response was measured in 83% (40 of 48). Referral patterns changed in 46% (22 of 48) of physicians who treated HCV. All respondents who did not treat HCV referred patients for consideration, with 90% (26 of 29) made to hepatologists. CONCLUSIONS: Chronic liver disease comprised <25% of practice in the majority of surveyed respondents. Among those who treated HCV, one-third have not prescribed a PI. Barriers to prescription and referral pattern changes are noted by those currently treating patients with HCV infection.